The transformation behaviour of "alucones", deposited by molecular layer deposition, in nanoporous Al2O3 layers - Van De Kerckhove, Kevin; Barr, Maissa K. S.; Santinacci, Lionel; Vereecken, Philippe M.; Dendooven, Jolien; Detavernier, Christophe (Dalton Transactions, 2018)
Nanoporous alumina films can be synthesized from hybrid organic-inorganic "alucone" films deposited by molecular layer deposition (MLD) by wet etching in deionized water or calcination in air at 500 °C. This transformation process was systematically investigated for two alucone chemistries based on ethylene glycol (EG) and glycerol (GL). Ellipsometric porosimetry (EP) was used for the characterization of the porous alumina structures that are formed as a result of the treatments. Etching in deionized water transforms both EG- and GL-alucones into porous alumina with a porosity of about 40%, albeit with a different pore structure: cylindrical pores for EG-alucones and ink-bottle structures for GL-alucones. Calcination in air up to 500 °C only successfully transformed EG-alucones into porous alumina if the chosen heating and cooling rate was lower than 200 °C h-1. Below this ramp rate, a relationship between the resulting porosity and the ramp rate was found. At the lowest investigated ramp rate of 20 °C h-1, the highest porosity of 36% was achieved. For this treatment type, the pore shape was of the ink-bottle type for all investigated ramp rates with narrow 1 nm-sized pores. Infrared spectroscopy (FTIR) and X-ray photoelectron spectroscopy revealed that the final chemistry of the porous structures was slightly different for both treatments due to trace amounts of carbon left behind by water etching. This suggests that the internal surface of the porous structure has a different termination depending on the chosen treatment. The precise thickness control and conformal nature inherent to MLD combined with the wet and heat treatments enables the coating of complex 3D structures with a porous alumina film with a well-defined thickness and pore structure.
Created from Fastlane, Scopus look-up